'We Have Certainly Saved Ourselves': Popular Views of Masculinity during the Korean War, 1950–53. (December 2014) - Lechner, Zachary J.
Abstract : This article addresses the ways in which the American popular media, particularly middle-brow magazines, novels, and films, created a gendered interpretation of the Korean War. On the US home front, cultural commentators linked the purported 1950s crisis of masculinity to concerns that "coddled" and "overmothered" American military personnel would lack the manly vigor necessary to prevent South Korea from falling to communist forces. Ultimately, though, most of these observers insisted that in the crucible of war lay an antidote for America's flagging masculine spirit. The so-called "police action" served as a critical terrain — both real and imagined — for debating masculinity during the Cold War. Although such optimism proved short-lived, this martial vision for boosting manliness resonated in post-war US policy and culture well beyond the three short years of the conflict.